Dietary patterns associated with colorectal cancer risk in the Malaysian population: a case-control study with exploratory factor and regression analysis - Ainaa Almardhiyah Abd Rashid; Lydiatul Shima Ashari; Nor Hamizah Shafiee; Raja Affendi Raja Ali; Lee Yeong Yeh; Mohd Razif Shahril; Hamid Jan Jan Mohamed (BMC, 2023)
Abstract Background Studies on the relationship between diet and colorectal cancer (CRC) risk using single food or nutrient approach are widely conducted as opposed to dietary pattern approach. Therefore, this study aimed to determine the major dietary patterns and their association with CRC risk among Malaysians. Methods Patients aged between 18 and 80 years old from two teaching hospitals in Peninsular Malaysia were recruited through purposive sampling. Socio-demographic information and anthropometry data were assessed before the colonoscopy procedure, and dietary intake was also recorded using a validated semi-quantitative food frequency questionnaire (FFQ). Cases were those patients having histopathologically proven CRC, while controls were those without. Results Four major dietary patterns were identified: the allergenic diet, plant-based diet, processed diet, and energy-dense diet pattern. After adjusting for potential covariates, the processed diet pattern was consistently associated with CRC (OR = 3.45; 95% CI = 1.25-9.52; P = 0.017) while the plant-based diet, energy-dense diet, and allergenic diet were not associated with CRC risk. Conclusions The processed diet pattern attributed to a diet high in confectionaries and fast foods was associated with an increased risk of CRC in the Malaysian population. In order to give prevention measures through lifestyle change, more research could be done on the effect of food patterns on faecal microbiota associated with CRC.